Quality of Life and Mental Health in Kidney Transplant Recipients During the COVID-19 Pandemic - De Pasquale, Concetta; Pistorio, Maria Luisa; Veroux, Pierfrancesco; Gioco, Rossella; Giaquinta, Alessia; Privitera, Francesca; Veroux, Massimiliano (Frontiers in Psychiatry, 2021)
Introduction The COVID-19 pandemic has led to an increase in mental distress such as phobic anxieties, depressive reactions, hypochondriac concerns, and insomnia. Among the causes are risk of infection and prolonged isolation. This study aimed to analyze psychopathological variables and dysfunctional lifestyles related to adequate therapeutic compliance in kidney transplant recipients. Methods Eighty-nine kidney transplant recipients were evaluated using an online protocol including a questionnaire concerning habits, lifestyle and psychophysical well-being in the COVID-19 period, the Middlesex Hospital Questionnaire (MHQ) and the SF-36 Health Survey to evaluate the perception of their physical and emotional health. Results Of these recipients, 28.6% reported changes in their emotional state. Sleep quality deteriorated for 16.1%. Anxiety (M = 5.57, r = 0.33; p <0.05) and phobia (M = 6.28, r = 0.26; p <0.05) correlated with concerns related to physical health. There was no negative impact on relational and socialization aspects, which were likely well compensated by the use of remote technologies such as video phone calls, Zoom meetings and use of computers (r = 0.99; r = 0.80; p <0.05). Conclusions It would be interesting to maintain this remote visit and interview mode to monitor, on a clinical and psychological level, kidney transplant recipients in subsequent follow-ups (12-18 months), to check for any psychopathological disorders and/or changes in their resilience capacity in the Coronavirus emergency.